The 'Ethical' COVID-19 Vaccine is the One that Preserves Lives: Religious and Moral Beliefs on the COVID-19 Vaccine. (19th July 2021) - Giubilini, Alberto; Minerva, Francesca; Schuklenk, Udo; Savulescu, Julian
Abstract: Although the COVID-19 pandemic is a serious public health and economic emergency, and although effective vaccines are the best weapon we have against it, there are groups and individuals who oppose certain kinds of vaccines because of personal moral or religious reasons. The most widely discussed case has been that of certain religious groups that oppose research on COVID-19 vaccines that use cell lines linked to abortions and that object to receiving those vaccine because of their moral opposition to abortion. However, moral opposition to COVID-19 vaccine research can be based on other considerations, both secular and religious. We argue that religious or personal moral objections to vaccine research are unethical and irresponsible, and in an important sense often irrational. They are unethical because of the risk of causing serious harm to other people for no valid reason; irresponsible because they run counter to individual and collective responsibilities to contribute to important public health goals; and in the case of certain kinds of religious opposition, they might be irrational because they are internally inconsistent. All in all, our argument translates into the rather uncontroversial claim that we should prioritize people's lives over religious freedom in vaccine research and vaccination roll out.